Brain processes in mothers and nulliparous women in response to cry in different situational contexts : a default mode network study - Rigo, Paola (2020)
Objective: In everyday life, parents must respond to and interact with children while in different situational contexts. How situational contexts influence parents’ responses has not been systematically studied. Here we investigated mothers’ versus nonmothers’ neural responses to infant vocalizations in different situations with different task demands. Design: Using fMRI in 21 women (10 mothers), we explored the effects of being distracted by self-oriented (self-referential decisions about personality adjectives) versus goal-oriented (syllabic counting of personality adjectives) tasks while listening to infant cry in comparison with other emotional sounds (infant laughing, adult crying) on the activity of two medial nodes of the Default Mode Network (DMN): the medial prefrontal cortex (MPFC) and posterior cingulate cortex (PCC). Results: In the self-oriented task while listening to infant cry, both mothers and nulliparas showed (weak) activation of the DMN; this response likely reflects a shift of attention from the task to the cry. In the goal-oriented task, mothers, not nulliparas, showed (weak) activation of the DMN; this result is compatible with interference of emotional sounds while attending to a goal-oriented task, an activity that deactivates the DMN. Conclusions: Mothers are prone to process infant cry and emotional sounds and are less distracted from doing so by situational contexts, demonstrating their greater sensitivity to emotional sounds such as cry. By contrast, situational context influenced brain responses to infant sounds in nulliparas.